Fonologi dan Leksikologi Bahasa Arab: Kajian Struktur Bunyi dan Kosakata dalam Perspektif Linguistik - Bahri, Samsul (Kartika: Jurnal Studi Keislaman, 2025)
This study focuses on two major subsystems in Arabic linguistics, namely phonology and lexicology, emphasizing their significance in the formation and comprehension of the Arabic language system. The research employs a library-based approach with a descriptive-analytical method. The discussion on lexicology includes the analysis of lexemes, lexons, and allolexes, as well as various mechanisms of word formation such as zero derivation, affixation, reduplication, shortening, back-derivation, and compounding. Meanwhile, phonology is examined on two levels: phonetics, which studies the physical properties of sounds without considering their semantic functions, and phonemics, which analyzes sounds as the minimal distinctive units that differentiate meaning. The findings indicate that a comprehensive understanding of sound structures (phonology) and vocabulary structures (lexicology) is essential for mastering Arabic in a systematic, effective, and functional manner. The main contribution of this research lies in affirming the interrelation between phonemes and lexemes in shaping the Arabic language system, while also highlighting the relevance of theoretical library research in deepening knowledge of Arabic as a complex and meaning-rich communication system.